Game over, Super Rabbit Boy! [#1] - Flintham, Thomas (New York, NY : Branches/Scholastic Inc., 2017)
When King Viking and his evil robot army attack Animal Town, and kidnap Singing Dog, it is up to Super Rabbit Boy, with some help from Sunny and his video game console, to save the day.
Keywords: Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Animals -- Juvenile fiction; Video games -- Juvenile fiction; Graphic novels